(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sutrisnawati, Ramadhan A. 2025. Molecular detection and phylogenetic analysis of Schistosoma japonicum in Central Sulawesi, Indonesia using COI gene. Biodiversitas 26: 4042-4047. Schistosomiasis, an endemic disease in several tropical regions, including Indonesia, is caused by Schistosoma japonicum, making its early detection crucial for controlling the spread. Molecular detection using the Cytochrome Oxidase 1 (COI) gene not only aids in diagnosing infections but also contributes to environmental DNA (eDNA) studies by detecting parasite DNA from environmental samples such as water or soil. This study aimed to detect Schistosoma japonicum in Central Sulawesi, Indonesia, using the COI gene as the molecular target. Fecal samples from individuals suspected of infection were collected from various endemic regions in the area. The Polymerase Chain Reaction (PCR) technique successfully amplified a 585 bp fragment of the COI gene, considered both sensitive and specific for S. japonicum detection. Out of the five samples analyzed, a number tested positive, and the resulting amplicons showed 99.21-99.52% sequence similarity with S. japonicum sequences in the GenBank database. Phylogenetic analysis placed these isolates within a well-supported clade together with S. japonicum from other parts of Indonesia and neighboring countries, confirming their close evolutionary relationship. Minor nucleotide variations were observed, suggesting potential local adaptations that may have epidemiological relevance. These results confirm the presence of S. japonicum in Central Sulawesi and demonstrate the utility of the COI gene in both detection and genetic characterization. The findings also highlight the value of incorporating molecular data into schistosomiasis surveillance to improve risk mapping, guide intervention priorities, and monitor possible drug resistance emergence. This approach complements traditional diagnostic methods, which often have reduced sensitivity in light infections. In conclusion, the COI gene provides a reliable tool for identifying and understanding the genetic diversity of S. japonicum in Indonesia. Future research should expand sample sizes and geographic coverage to further elucidate the population structure of S. japonicum and support more targeted, sustainable schistosomiasis control strategies locally and globally.